(untitled) (University of Khartoum Engineering Journal, 2022)
This paper investigates the effect of ethanol-gasoline blends on fuel properties characteristics of variable speed spark ignition (SI) engines using standard laboratory methods. Fuel properties tests were conducted for density, API gravity, kinematic viscosity, cloud point, flash and fire point, heat value, distillation and Octane number using ethanol-gasoline blends with different percentages of ethanol. The blends selection was based on successful completion of engine standard short test carried out on a computerized four cylinders, four stroke, and variable speed SI engine with eddy current dynamometer and data logging facilities. Fuel properties test results showed that blends densities and kinematics viscosity increased continuously and linearly with increasing percentage of ethanol, while API gravity and heat value decreased with decreasing percentage of ethanol. Furthermore, cloud point, flash and fire points for blends were found to be higher than pure gasoline fuel, while distillation curves were lower. The tested blends Octane rating based on Research Octane Number (RON) increased continuously and linearly with increasingpercentage of ethanol. Results from this study will be valuable on the assessment of the suitability of ethanol-gasoline blends as bio-fuel for automotive industry to cater for the country needs.